Pengaruh Disiplin Kerja Terhadap Produktivitas Kerja Pegawai (Studi Kasus Pada PT. BPR Syariah Harum Hikmah Nugraha Leles Garut) - Nadia Febriani; Abdurrahman Rahim Thaha (eCo-Buss, 2024)
This study examines the effect of work discipline on employee productivity at PT. BPR Syariah Harum Hikmah Nugraha Leles Garut. Work discipline is one of the important factors that contribute to improving employee performance. The purpose of this study is to understand the extent to which work discipline affects employee productivity in the company. The approach used in this research is quantitative method with descriptive and associative analysis. Quantitative data were collected through distributing questionnaires to employees of PT BPR Syariah Harum Hikmah Nugraha Leles Garut. Data analysis techniques include validity test, reliability test, correlation test, determination test, and hypothesis testing. The results showed a strong correlation between work discipline and work productivity. Work discipline is proven to have a positive and significant influence on employee work productivity. Based on these findings, the management of PT BPR Syariah Harum Hikmah Nugraha is advised to improve stricter work discipline policies and provide training and development to strengthen work discipline. These steps are expected to encourage an increase in overall work productivity in the company.